The Effect of Time Management on Employee Performance - Royan Kusniyanto; Mutiara Fitridiani; Yusniati Sihombing; Monica Damayanti; Muhammad Saeful Haddy (PT. Keberlanjutan Strategis Indonesia, 2025)
Purpose:This study aims to analyze the effect of time management on employee performance. The research employed a quantitative approach using a survey method, with data collected through questionnaires distributed to 60 respondents.Methodology:Simple linear regression analysis was applied to examine the relationship between variables, supported by validity and reliability tests as well as classical assumption testing. The results indicate that time management has a positive and significant effect on employee performance, as evidenced by a t-value of 6.673 with a significance level of 0.000.Findings:Furthermore, the coefficient of determination shows an R-squared value of 0.434, meaning that time management contributes 43.4% to employee performance, while the remaining 56.6% is influenced by other factors not examined in this study. These findings suggest that effective time management plays a crucial role in improving employee productivity and work outcomes. The study highlights the importance of implementing structured time management practices within organizations to enhance employee performance.Implication:Future research is recommended to incorporate additional variables such as motivation, leadership, and work environment to obtain a more comprehensive understanding of factors affecting employee performance.